Pemberdayaan Ekonomi Masyarakat Melalui Pengembangan Potensi Lokal Budidaya Black Soldier Fly (Maggot) di Desa Sukaratu Karawang - Rohma Septiawati; Devi Astriani; Moch Agus Ariffianto (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2021)
Law on National Development Planning System (Number 25/2004) mandates that Development planning must refer to the consideration that the goal of development of all government levels is the same, namely the welfare of the community. Empowerment is a concept to give people greater responsibility for how to do work. The potential of Sukaratu village consists of agriculture, livestock, tourism objects, handicrafts, cultivation and plantations. Among these potentials, the authors take the economic empowerment potential of cultivating black soldier fly maggot as an alternative ingredients for fish feed and reducing organic waste, so that it can increase the income of the people of Sukaratu. The research method used is qualitative and quantitative research; observation and interviews in an effort to obtain data. The results showed that the potential of Sukaratu village consisted of agriculture, animal husbandry, tourism objects, handicrafts, cultivation and plantations, the potential of human resources in terms of age and education was good, but in terms of business creativity and business skills, need to be improved. Maggot cultivation can reduce organic waste. The capital is not large enough because it only requires terraced media and houses that are given nets for broodstock to lay eggs.